Development of Web-Based Indonesian Teaching Materials on Listening Materials for Grade X High School Level - Pradicta Nurhuda; Kaniah; Dwi Wahyuni; Harini (Indonesia Approach Education, 2024)
In learning Indonesian language, the existence of innovative teaching materials in line with technological developments is one of the right efforts in improving student learning outcomes. Listening material is one of the achievements per element that students must learn in learning Indonesian high school grade X according to the Merdeka Curriculum. This research focuses on the development of teaching materials and knowing the feasibility of web-based teaching materials on listening materials. The purpose of this research is to find out the analysis of teaching material needs, the development of teaching materials, and the feasibility test of web-based teaching materials on listening materials. This research uses the development method or Research and Development (R&D) with the ADDIE model approach. Data collection is carried out by observation, interviews, filling out questionnaires. The needs analysis sample was conducted on 2 Indonesian language teachers and 20 grade X students at SMAN 4 Bekasi City, SMAN 12 Bekasi City, and SMA Strada Bekasi City. Meanwhile, product trial samples were carried out on 2 Indonesian teachers and 36 grade X students at SMAN 12 Bekasi City. The results of the needs analysis are (1) teachers and students need teaching materials on listening materials that can display audio or audio visual that can be accessed through devices anywhere and anytime; (2) web-based teaching materials are developed through three steps, namely from starting to create designs, registering domains, to developing teaching materials using WordPress media; and (3) The results of the teaching material validation test by linguists were declared very feasible with a percentage of 88%, material expert validation was declared very feasible with a percentage of 92%, and media expert validation was declared feasible with a percentage of 80%, while the results of teaching material trials by teachers were declared feasible with a percentage of 80% and teaching material trials by students were declared very feasible with a percentage of 82%. The conclusion of the research is web-based teaching materials Indonesian listening materials that can be accessed through https://bahanajarkelas10.site/ link suitable for use by teachers and grade X high school students.